SOFTWARE FOR DETERMINATION OF BEHAVIOR PATTERNS OF WEBFORUM MEMBERS - Syerov, Yuriy; Kravets, Ruslan (International Journal of Computing, 2014)
Article considers actual problem of Web-forums’ members’ behavior and classifying information system development. In the article existing Web-forum CMS’ were analyzed, process of Web-community members’ behavior analyzing was researched and overviewed, the process of information system developing was described.